Ca2+-dependent rapid uncoupling of astrocytes upon brief metabolic stress - Eitelmann, Sara; Everaerts, Katharina; Petersilie, Laura; Rose, Christine R.; Stephan, Jonathan (Frontiers in Cellular Neuroscience, 2023)
Astrocytic gap junctional coupling is a major element in neuron–glia interaction. There is strong evidence that impaired coupling is involved in neurological disorders. Reduced coupling was, e.g., demonstrated for core regions of ischemic stroke that suffer from massive cell death. In the surrounding penumbra, cells may recover, but recovery is hampered by spreading depolarizations, which impose additional metabolic stress onto the tissue. Spreading depolarizations are characterized by transient breakdown of cellular ion homeostasis, including pH and Ca2+, which might directly affect gap junctional coupling. Here, we exposed acute mouse neocortical tissue slices to brief metabolic stress and examined its effects on the coupling strength between astrocytes. Changes in gap junctional coupling were assessed by recordings of the syncytial isopotentiality. Moreover, quantitative ion imaging was performed in astrocytes to analyze the mechanisms triggering the observed changes. Our experiments show that a 2-minute perfusion of tissue slices with blockers of glycolysis and oxidative phosphorylation causes a rapid uncoupling in half of the recorded cells. They further indicate that uncoupling is not mediated by the accompanying (moderate) intracellular acidification. Dampening large astrocytic Ca2+ loads by removal of extracellular Ca2+ or blocking Ca2+ influx pathways as well as a pharmacological inhibition of calmodulin, however, prevent the uncoupling. Taken together, we conclude that astrocytes exposed to brief episodes of metabolic stress can undergo a rapid, Ca2+/calmodulin-dependent uncoupling. Such uncoupling may help to confine and reduce cellular damage in the ischemic penumbra in vivo.